Hydroxyurea and nonmelanoma skin cancers: report on three cases and review of the literature - Roš, Tatjana; Gajić, Branislava; Gajinov, Zorica; Ivkov Simić, Milana; Stojanović, Slobodan; Golušin, Zoran (Vojnosanitetski pregled, 2017)
Introduction. Hydroxyurea (HU) is a cytostatic agent, frequently used for the treatment of myeloproliferative disorders, sickle cell anemia and severe forms of psoriasis. Cutaneous side effects occur in up to one third of patients taking hydroxyurea, with the most serious side effect being susceptibility to develop non-melanoma skin cancers. Case report. We report  3 patients using HU that have developed multiple skin malignancies on the head and neck region and dorsa of the hands, arranged according to the level of the overall squamous dysplasia expressed. Conclusion. A cumulative dose of hydroxyurea affects skin cancer promotion in concordance with other risk factors determining cumulative ultraviolet exposure (age of the patients, skin phototype, sun habits), but the exact influence of each of them and enrollment of other possible cofactors remains to be elucidated. We point out the importance of adequate skin cancer preventive and therapeutic approach to the patients treated with hydroxyurea.
Keywords: skin neoplasms; ultraviolet rays; hydroxyurea; treatment outcome